Lecture 11. Global Warming: Why, When, and How - Donald R. Blake (University of California Irvine (UCI), 2013)
(en)UCI Chem 1B is the second quarter of General Chemistry and covers the following topics: properties of gases, liquids, solids; changes of state; properties of solutions; stoichiometry; thermochemistry; and thermodynamics. Index of Topics: 0:01:26 Global Warming Theory 0:05:11 Why should we care? 0:18:56 Sun's Radiation Hitting Earth 0:20:34 Solar Terrestrial Radiation 0:23:09 What Makes a Gas a Greenhouse Gas 0:27:59 Sherry Rowland's Hand-Drawn Radiance Graph 0:31:32 Solar Radiation Hitting the Atmosphere 0:36:18 Sherry Rowland's Radiance Graph 0:37:38 What about the greenhouse gases & aerosols 0:41:06 Global Fossil-Fuel CO2 Annual Emissions 0:42:27 An Atlas of Pollution 0:43:42 Per Capita CO2 Emissions 0:44:05 Cumulative CO2 Emissions 0:45:31 Atmospheric CO2 at Mauna Loa Observatory 0:46:50 CO2, CH4, and Estimated Global Temperature 0:49:50 Paleoclimate Temperature Change 0:51:04 Temperature Change Consistent with Greenhouse Gases? 0:52:36 Increasing Melt Area on Greenland 0:54:12 Sea Ice Area 0:55:32 What Causes Sea Level Rise? 1:00:41 Myths or Spin 1:02:27 Infinity Pool Analogy 1:04:22 Fred Singer 1:05:02 Latest Global Temperature Data 1:06:13 Global Cooling 1:07:49 Ozone was the 80's AGW